Analisis Peningkatan Ekosistem Logistik (Ekspor dan Impor) Pada Pelindo Multi Terminal Belawan - Ade Irma Sofyan Nasution (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to determine the improvement of the logistics ecosystem both from exports and imports at Pelindo Multi Terminal Belawan. Where Pelindo Belawan is the largest port in North Sumatra, however, due to the improvement in the logistics ecosystem, many goods have to transit before arriving at the Belawan Port dock. Apart from that, it can carry out port activities appropriately and maximize aspects of office effectiveness in order to create work comfort and optimal performance for its employees. If employees and service users who work feel comfortable and satisfied then their performance at Pelindo Multi Terminal Belawan will also be good. This study uses a qualitative method.